2023
DOI: 10.3390/buildings13020339
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Literature Review Using Placemaking Theories to Unravel Student Social Connectedness in Hybrid University Learning Environments

Abstract: Student social connectedness is indicated to be changing with the increasing digitalisation of universities. This narrative literature review aims to bring new meanings to the hybrid university learning environment (HULE), and to develop a framework for the benefit of student social connectedness by using placemaking theories. It searches through the academic literature for evidence of experience with three attributes of social connectedness: socialising, social support, and sense of belonging, in relation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Sociomateriality offers a theory to understand how social aspects are embedded in material objects, which is important when considering the digital and physical space relationally. Placemaking brings a focus on the environment, which has often been overlooked by pedagogic research [8]. Drawing on the concept of 'sense of place', this article enables consideration of social connection to place, and it is possible to explore how people identify with a place, develop a sense of belonging or attachment, and develop identities and social mobility.…”
Section: The Theoretical Way Of Thinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sociomateriality offers a theory to understand how social aspects are embedded in material objects, which is important when considering the digital and physical space relationally. Placemaking brings a focus on the environment, which has often been overlooked by pedagogic research [8]. Drawing on the concept of 'sense of place', this article enables consideration of social connection to place, and it is possible to explore how people identify with a place, develop a sense of belonging or attachment, and develop identities and social mobility.…”
Section: The Theoretical Way Of Thinkingmentioning
confidence: 99%
“…Conceived initially as the perceived loss of a 'sense of place' during the architectural dystopia of the urban renewal era, placemaking is influenced by a variety of disciplines, primarily Jane Jacob's neighbourhood activism [32]. Placemaking can be thought of as a way of improving the quality of public places which have a community entwined, but it has also been applied in research outside of the public space in private places, for example, see [33,34], which makes it a suitable framework to apply for the HULE [8,15]. In the learning environment, placemaking has been applied by Poplin et al [35] to help understand how students feel and describe certain places.…”
Section: Placemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Social connectedness in university students is changing following the steady integration of technology into the university and the restrictions of the COVID-19 pandemic (Eyal and Gil, 2022;Van der Meer et al, 2021;Wheele et al, 2023). This digitally-enabled style of learning tends to be favoured by students in universities as it can bring a more up-to-date and less rigid approach to the learning environment (Doghonadze et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It offers greater and constant access to knowledge and communication streams, and increased flexibility (Van der Meer et al, 2021) in comparison to more rigid approaches, such as traditional on-site learning or online learning where there is an absolute loss of the university as a physical place (Allen and McLaren, 2022). This mix of online and on-site learning either synchronously or asynchronously referred to in this article as the hybrid university learning environment (HULE), is believed to have great potential and is often considered desirable by students (Allen and McLaren, 2022;Bülow, 2022;Raes et al, 2022;Swist and Kuswara, 2016;Wheele et al, 2023). However, as the pandemic evolved, architectural industry research indicated that social connectedness as part of the overall university experience is negatively impacted in the HULE (Bülow, 2022;Doghonadze et al, 2021;Eyal and Gil, 2022;Raes et al, 2020;Swist and Kuswara, 2016;Triyason et al, 2020;Van der Meer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%